PECULIARITIES OF MORPHOGENESIS AND VARIANT ANATOMY OF THE MANDIBLE IN HUMAN FETUSES - Tsyhykalo О.V.; Palis, S.Yu. (World of Medicine and Biology, 2018)
In order to determine the regularities of morphogenesis, variant anatomy and dynamic peculiarities of space-time changes in the mandibular structure at the early period of human ontogenesis 60 specimens of human fetuses 160,0-450,0 mm of their parietal-coccygeal length (4-9th months of the intrauterine development) were examined using a complex of traditional and up-to-date methods of morphological study (anthropometry, computed tomography, morphometry, making the series of sequential histologic sections, microscopy, three-dimensional computer reconstruction, statistical analysis). The regularities of individual anatomical variability, sex-age and constitutional peculiarities of the mandibular structure in the fetal period of human ontogenesis are determined. Critical periods of ontogenesis of mandibular morphogenesis at the pre-natal term of human ontogenesis are detected. Reconstructive and mathematical models of the mandible to determine its functional morphology and embryo topography are designed.